Meiosis-Based Laboratory Evolution of the Thermal Tolerance in Kluyveromyces marxianus - Wu, Li; Lyu, Yilin; Wu, Pingping; Luo, Tongyu; Zeng, Junyuan; Shi, Tianfang; Zhou, Jungang; Yu, Yao; Lu, Hong (Frontiers in Bioengineering and Biotechnology, 2022)
Kluyveromyces marxianus is the fastest-growing eukaryote and a promising host for producing bioethanol and heterologous proteins. To perform a laboratory evolution of thermal tolerance in K. marxianus, diploid, triploid and tetraploid strains were constructed, respectively. Considering the genetic diversity caused by genetic recombination in meiosis, we established an iterative cycle of "diploid/polyploid - meiosis - selection of spores at high temperature" to screen thermotolerant strains. Results showed that the evolution of thermal tolerance in diploid strain was more efficient than that in triploid and tetraploid strains. The thermal tolerance of the progenies of diploid and triploid strains after a two-round screen was significantly improved than that after a one-round screen, while the thermal tolerance of the progenies after the one-round screen was better than that of the initial strain. After a two-round screen, the maximum tolerable temperature of Dip2-8, a progeny of diploid strain, was 3 ℃ higher than that of the original strain. Whole-genome sequencing revealed nonsense mutations of PSR1 and PDE2 in the thermotolerant progenies. Deletion of either PSR1 or PDE2 in the original strain improved thermotolerance and two deletions displayed additive effects, suggesting PSR1 and PDE2 negatively regulated the thermotolerance of K. marxianus in parallel pathways. Therefore, the iterative cycle of "meiosis - spore screening" developed in this study provides an efficient way to perform the laboratory evolution of heat resistance in yeast.